Relationship among soil properties, root-lesion nematode population, and soybean growth - Franchini, Julio Cezar; Debiasi, Henrique; Dias, Waldir Pereira; Ribas, Luiz Nery; Silva, João Flavio Veloso; Balbinot Junior, Alvadi Antonio (Revista de Ciências Agroveterinárias, 2018)
Root-lesion nematode (RLN) (Pratylenchus brachyurus) is an important challenge to soybean production in Central Brazil due to its widespread occurrence, along with the absence of resistant cultivars and strategies for its management. The aim of this research was to evaluate the relationship among soil properties, RLN populations, and soybean crop growth using geostatistical analysis. The experiment was conducted in a soybean field located in the northern half of Mato Grosso state, in Brazil, with a history of damages by RLN. The results suggest a positive correlation between plant height and values of pH, Ca, Mg, and base saturation. On the other hand, RLN population was positively correlated with organic carbon, cation exchange capacity, and soil potential acidity. Moreover, our findings also indicate that soybean plant growth is reduced under acidic soil conditions, as susceptibility to RLN increases. Thus, the correction of soil acidity to suitable levels for soybean crop becomes an important strategy to minimize damages by RLN.